β-Hydroxy-β-methyl butyrate (HMB) supplementation elevates testosterone levels without significant changes to cortisol, IGF-1, or growth hormone in adults: a GRADE-assessed systematic review and meta-analysis of controlled trials - Bideshki, Mohammad Vesal; Sadeghi, Behrad; Behzadi, Mehrdad; Jozi, Hannane; Eskandari Damaneh, Hadi; Rashidinejad, Ali (Frontiers in Nutrition, 2025)
Background and aimIncreasing interest in improving physical performance and muscle mass in adults has highlighted the potential benefits of β-hydroxy-β-methyl butyrate (HMB) supplementation. While numerous studies have been conducted in this area, the hormonal response to HMB remains unclear. We hypothesized that HMB supplementation would significantly increase anabolic hormone levels, particularly testosterone, while not affecting the cortisol, IGF-1, or growth hormone levels in adults.MethodsA comprehensive search of databases, including PubMed, Web of Science, and Scopus, was performed to identify relevant studies until January 2024. The protocol was registered with Prospero (CRD42024552074). The studies evaluated the impact of HMB supplementation on hormonal outcomes, including testosterone, cortisol, insulin-like growth factor-1 (IGF-1), and growth hormone (GH). Utilizing a random-effects model, the standardized mean differences (SMDs) and their corresponding 95% confidence intervals (CIs) were computed, and the GRADE framework was applied.ResultsA total of 15 controlled trials (CTs) comprising 712 participants were included. HMB supplementation significantly increased testosterone levels (SMD: 0.82, 95% CI: 0.35, 1.29, p = 0.001). However, no significant changes were observed in the cortisol (SMD: −0.39, 95% CI: −0.92, 0.14, p = 0.14), IGF-1 (SMD: −0.18, 95% CI: −0.54, 0.18, p = 0.33), and GH (SMD: 0.04, 95% CI: −0.73, 0.82, p = 0.91) levels. According to the GRADE criteria, the quality of evidence was rated as ranging from low to high.ConclusionHMB supplementation significantly elevates testosterone levels in adults without distinct impacts on other hormonal pathways. However, it does not appear to significantly influence the cortisol, IGF-1, or GH levels.